Corticosterone and vitamin A concentrations in tree swallow (Tachycineta bicolor) nestlings exposed to environmental contaminants along the St. Lawrence River, Canada and United States of America. - Martinovic, Barbara. (University of Ottawa (Canada), 2002)
In 1999 and 2000 reproductive success and chemical biomarkers were measured in 16 day old tree swallows (Tachycineta bicolor) collected from nine sites along the St. Lawrence River in Canada and USA. Chicks were collected for analysis of organochlorine pesticides, polychlorinated biphenyls (PCBs), total mercury, polychlorinated dibenzodioxins (PCDDs), and polychlorinated dibenzofurans (PCDFs), and measures of corticosterone response, and vitamin A concentrations. Study sites were located in the vicinity of landfill sites and industrial outfalls in the St. Lawrence River area of concern (AOC). Altered vitamin A metabolism and corticosterone homeostasis in wildlife exposed to contaminants may lead to numerous effects on reproduction, growth, and immune function. Overall these data suggest that current levels of organochlorine contamination may be affecting the hypothalamo-pituitary-adrenal axis and vitamin A levels in environmentally exposed tree swallow nestlings along the St. Lawrence River. (Abstract shortened by UMI.)
Keywords: Biology, Ecology.